Theoretical basis for nursing - McEwen, Melanie; Wills, Evelyn M. (Philadelphia, Pennsylvania : Wolters Kluwer, 2023)
Providing an essential overview of nursing theory in a single, straightforward text, Theoretical Basis for Nursing, 6th Edition, equips students with the knowledge and understanding to apply nursing theory to practice and improve as nurses. Unlike some nursing theory texts, this AJN Award-winning resource goes beyond demonstrating the application of theory to teach students$1 (Bregardless of their level of experience in theory$1 (Bto think critically and analyze, evaluate, and apply theories with confidence.s
Unit I: Introduction to Theory -- Chapter 1. Philosophy, Science, and Nursing -- Chapter 2. Overview of Theory in Nursing -- Chapter 3. Concept Development: Clarifying Meaning of Terms -- Chapter 4. Theory Development: Structuring Conceptual Relationships in Nursing -- Chapter 5. Theory Analysis and Evaluation -- Unit II: Nursing Theories -- Chapter 6. Overview of Grand Nursing Theories -- Chapter 7. Grand Nursing Theories Based on Human Needs -- Chapter 8. Grand Nursing Theories Based on Interactive Process -- Chapter 9. Grand Nursing Theories Based on Unitary Process -- Chapter 10. Introduction to Middle-Range Nursing Theories -- Chapter 11. Overview of Selected Middle-Range Nursing Theories -- Chapter 12. Evidence-Based Practice and Nursing Theory -- Unit III: Shared Theories Used by Nurses -- Chapter 13. Theories From the Sociologic Sciences -- Chapter 14. Theories From the Behavioral Sciences -- Chapter 15. Theories From the Biomedical Sciences -- Chapter 16. Theories, Models, and Frameworks From Leadership and Management -- Chapter 17. Learning Theories -- Chapter 18. Ethical Theories and Principles -- Unit IV: Application of Theory in Nursing -- Chapter 19. Application of Theory in Nursing Practice -- Chapter 20. Application of Theory in Nursing Research -- Chapter 21. Application of Theory in Nursing Administration and Management -- Chapter 22. Application of Theory in Nursing Education -- Chapter 23. Future Issues in Nursing Theory.
Includes index.
Keywords: NURSING